"I'm strong...I feel sicker when I'm at home than when I'm working". Man-commodity and health in bricklayers. - Juan Carlos Maqueda Hernandez; Ricardo Cuellar Romero; Margarita Pulido Navarro (Social Medicine Publication Group, 2022)
This paper presents the experiences and the meaning that two bricklayers, father and son, give to their bodies, in the context of a capitalist society governed by the trend towards the universalization of commerce. Some of Karl Marx's and Georg Lukács' approaches to the concepts of alienation and reification are taken up. It is considered that their heuristic scope transcends the space and time of the foundational process of immediate production in such a way that they open up a dialogue between the structural and the experiential, between the material and the emotional, between meanings. It is of particular interest to rescue, through the help of social history and oral history, the perceptions of the workers mentioned in relation to their health-illness process. Key words: alienation, reification, working time, social history, oral history, health-illness, bricklayers.